Islands in the clickstream reflections on life in a virtual world - Thieme, Richard; Briney, Andrew (Rockland, MA : Syngress Pub. : Distributed by O'Reilly & Associates, 2004)
CNN called Richard Thieme "a member of the cyber avant-garde". Digital Delirium named him "one of the most creative minds of the digital generation". Now Richard Thieme's wisdom on the social and cultural dimensions of technology is available in a single volume. "Islands in the Clickstream" ranges beyond the impact of technology to spirituality, psychological insight, and social commentary. Now that people are used to living in virtual worlds and move easily between online and offline worlds, they want to connect that experience to the deeper issues of our lives, including spiritual issues. Some examples include "Dreams Engineers Have", "The Crazy Lady on the Treadmill", and "Whistleblowers and Team Players". These essays raise serious questions for thoughtful readers. They have attracted favorable commentary from around the world and a fanatic, almost rabid fan base. * This author has become an extremely popular and highly visible talking head. He is a rare "personality" in the otherwise bland world of technology commentators. * The book leverages the loyalty of his audience in the same way Bill O'Reilly's "The O'Reilly Factor" and Al Franken's "Lies and the Lying Liars Who Tell Them" do. * The book is an easy read intended to provoke thought, discussion and disagreement.
Keywords: Technology -- Social aspects; Computers and civilization; Electronic books